Exploring the Use of Herbal Medicines and Digital Media in Maternal Health: A Review of Practices Among Indonesian Pregnant Women - Syarif, Alwiyah Nur; Mau, Muliadi; Sonni, Alem Febri (SAMATA JOURNAL OF PUBLIC HEALTH SCIENCE, 2025)
Despite the longstanding use of herbal remedies to support maternal health, particularly during lactation, existing research has yet to systematically explore the intersection of traditional practices, digital media influence, and public trust. This study aims to analyze how herbal beliefs are represented, trusted, and potentially distorted through digital platforms, and to assess the effectiveness of herbal interventions in enhancing breast milk production in Indonesia. Employing a systematic literature review methodology in accordance with PRISMA guidelines, the study examined 24 peer-reviewed articles sourced from Google Scholar, focusing on public perception, misinformation, and trust in herbal remedies. Additionally, 25 studies on breastfeeding interventions were reviewed to evaluate the outcomes of herbal-based and educational approaches. Results indicate that while herbal galactagogues such as Moringa leaves, katuk, and dates consistently improve lactation outcomes, digital media plays a dual role—facilitating both accurate health education and the spread of unverified claims. Educational interventions enhanced maternal understanding and acceptance of herbal remedies, especially when supported by community engagement and digital tools. However, variations in efficacy across contexts and limited clinical validation signal the need for more rigorous trials. The findings underscore the importance of culturally integrated, evidence-based strategies in maternal health promotion and call for the careful regulation of online health information to safeguard public trust and maternal well-being.